Distinct clinical features of transplanted children with Parvovirus B19 infection - Ran Jia; Lingfeng Cao; Lijuan Lu; Huaqing Zhong; Menghua Xu; Pengcheng Liu; Xunhua Zhu; Liyun Su; Jin Xu (Virology Journal, 2024)
Abstract Background The immature and suppressed immune response makes transplanted children a special susceptible group to Parvovirus B19 (PVB19). However, the clinical features of transplanted children with PVB19 infection haven’t been comprehensively described. Methods We searched the medical records of all the transplant recipients who attended the Children’s Hospital of Fudan University from 1 Oct 2020 to 31 May 2023, and reviewed the medical literature for PVB19 infection cases among transplanted children. Results A total of 10 cases of PVB19 infection were identified in 201 transplanted children at our hospital, and the medical records of each of these cases were shown. Also, we retrieved 40 cases of PVB19 infection among transplanted children from the literature, thus summarizing a total of 50 unique cases of PVB19 infection. The median time to the first positive PVB19 DNA detection was 14 weeks post-transplantation. PVB19 IgM and IgG were detected in merely 26% and 24% of the children, respectively. The incidence of graft loss/dysfunction was as high as 36%. Hematopoietic stem cell transplant (HSCT) recipients showed higher PVB19 load, lower HGB level, greater platelet damage, lower PVB19 IgM/IgG positive rates, and more graft dysfunction than solid-organ transplant (SOT) recipients, indicating a more incompetent immune system. Conclusions Compared with the published data of transplanted adults, transplanted children displayed distinct clinical features upon PVB19 infection, including lower PVB19 IgM/IgG positive rates, more graft dysfunction, and broader damage on hematopoietic cell lines, which was even more prominent in HSCT recipients, thus should be of greater concern.